Comparison of real-time PCR, indirect immunofluorescence antibody assay, and different staining techniques for the diagnosis of Pneumocystis jirovecii (Annals of Medical Research, 2021)
Aim: Pneumocystis pneumonia (PCP), caused by Pneumocystis jirovecii (P. jirovecii), is an opportunistic infection with a severe progression, often observed in immunocompromised patients. The diagnosis is difficult due to the non-specific clinical and radiological findings. Therefore, rapid and accurate diagnosis of the agent is important in terms of timely implementation of the treatment. In this study, it was aimed to detect P. jirovecii by Giemsa staining, Modified Toluidine Blue O staining (MTolB), indirect immunofluorescent antibody (IIFA) assay, and real-time polymerase chain reaction (PCR) in clinical samples obtained from patients suspected of having PCP.Material and Methods: Respiratory tract samples (23 oral wash, 19 bronchoalveolar lavage fluid, and eight induced sputum samples) of 50 patients referred to the Microbiology Laboratory of Gazi University Health Application and Research Hospital with the suspicion of PCP were analyzed. The presence of P. jirovecii in the respiratory tract samples was investigated by Giemsa staining, MTolB staining, IIFA (Pneumocell, Cellabs Pty Ltd, Australia), and real-time PCR (the primers targeting the DHFR gene).Results: Of the 50 samples included in the study, four (8%) with MTolB, five (10%) with Giemsa, seven (14%) with IIFA, and seven (14%) with real-time PCR were positive. When real-time PCR was accepted as the gold standard, the sensitivity and specificity values were found to be 85.7% and 97.7%, respectively for IIFA, 71.4% and 100%, respectively for Giemsa and 57% and 100%, respectively for MTolB. There was almost perfect agreement between the results of real-time PCR and IIFA (κ=0.92). In the comparison between PCR and cytochemical staining methods, Giemsa had almost perfect agreement with PCR (κ=0.92) and had a higher coefficient compared to MTolB (κ=0.88). Conclusion: It is considered that it would be more beneficial to use IIFA and real-time PCR tests together in the diagnosis of P. jirovecii.
Keywords: Pneumocystis jirovecii; giemsa; MTolB; IIFA; real-time PCR